Vocational higher secondary education in agriculture in Kerala - a multimidensional analysis - Kumari Sushama N P (Department of Agricultural Extension, College of Agriculture, 1993)
The study aimed at analysing the various dimensions of vocational Higher Secondary Education in Agriculture (VHSEA) in Kerala and to suggest a model for strengthening the same. The study was undertaken in nine VHSEA schools spread over eight districts in Kerala, where the scheme was first introduced in 1983-84 and where VHSEA courses are still being offered. There were 300 student-respondents for the study, viz. 150 respondents who have passed VHSEA from these nine schools during 1986-87, 1987-88 & 1988-89 and 50 each of VHSEA students undergoing PP,F & V and NM & OG courses in these schools at the time of the investigation, selected using probability proportion to size-random sampling. Besides, all the available teachers of VHSEA numbering 36 and 60 randomly selected experts from the State Department of Agriculture, Kerala Agricultural University and the Directorate of VHSE also formed the other categories of respondents for the study. The dependent variables were the student-respondents’ knowledge about the subject matter of the VHSEA Courses, attitude towards VHSEA programme, attitude towards scientific agriculture and evaluate perception of VHSE courses in agriculture. These variables were quantified using standardized measurement devices developed for the study. Ten independent variables were selected and quantified with the help of available procedures. Vocational interest areas, vertical mobility and employment status and factors affecting vertical mobility and employment status were also collected from the student-respondents. Data on the evaluative perception of VHSE courses in agriculture, evaluation of VHSEA syllabi and factors affecting vertical mobility and employability were gathered from the teachers of VHSEA and the experts. Constraints in and suggestions for improvement of VHSEA were also collected from the students and teachers of VHSEA. Pre-tested and structured interview schedules/questionnaires were used for data collection. The study revealed that majority of the student – respondents hailed from rural areas with agricultural background, they had secured low marks in SSLC/VHSEA and their family educational status and economic status were poor. Majority of them had high level of aspiration, and a sizeable number did not have financial support for starting self employment ventures. Majority of the student-respondents had only medium level of knowledge and favourable attitude towards VHSEA programme and scientific agriculture. Majority of the respondents had rated the VHSE courses in agriculture as ‘moderate’ the independent variable significantly influencing the dependent variables in general were marks obtained in SSLC, caste, family economic status, family educational status, level of aspiration (past, present and future) and finance for self employment. Commercial flower production and general agriculture were the most preferred vocational interest areas. Half of the VHSEA certificate holders were studying in degree classes and more than one fourth of them were not continuing their studies. Majority of the VHSEA certificate holders were unemployed. Over six per cent of them were working as Lab assistants and only two respondents were engaged in self employment avenues. Interest in higher education, job opportunities due to higher qualification and attitude towards higher education were the most important factors influencing their vertical mobility while awareness about the avenues for self employment, skill training for doing self employment and interest in taking up self employment were the most important factors influencing their employability. The teachers and experts in general rated the VHSEA as moderate. Low standard of pupils, lack of library facilities, lack of building facilities and lack of facilities for doing practicals were the most important constraints. Permanent teachers should be employed, scholarships and grants should be provided, provision for higher education, job opportunities to the pass outs and public should be made aware of the relevance of the VHSEA were the important suggestions for improvement of VHSEA. Based on the results of the study, a model to strengthen VHSEA in Kerala is suggested.